LANGUAGE EDUCATION AS A RESULT OF LEARNING THE LANGUAGE AND CULTURE OF THE PEOPLE - Sharipova, Sitora Khaidarovna (GOLDEN BRAIN, 2024)
This article examines issues of language teaching: problems of language education, the system of scientific knowledge related to the subject of study, the subject of speech activity. The current state of language education, the need to prepare an independent user of the language, as well as the components of communicative competence are presented. In addition, the current state of linguistics is outlined. The main subjects of linguistics: speech, speech activity, subject of speech, speech behavior, real processes of formation of speech communication, its acquisition and conditions.